(untitled) (Bangladesh Journal of Botany, 2021)
Evaluation of the antimicrobial, antiparasitic and phytochemical potential of medicinal plant Chenopodium album (Bathua) leaves extract was carried out. The plant extracts were prepared by using distilled water and methanol as an extraction solvents. Pure methanolic extract of leaves showed 15 mm against Staphylococcus auerus after 24 hrs. Aqueous extract showed no activity against S. auerus. Similarly in case of S. typhi pure methanolic leaves extract showed 13 mm. While standard discs gentamicin showed (DIZ) 18 mm after 24 hrs, different dilution inhibition zone was maximum in case of 100% pure extract, and decreased with increasing dilution. Minimum DIZ was observed at 25% and no zone at 5% dilution. Anthelmintic activity of crude methanolic extract of C. album leaves were tested, all extracts showed maximum corrected mortality of 100%, aqueous extract showed better antiparasitic activity than methanolic extract. It can be a potential source of therapeutic agent. Further analysis is needed for clinical trial. Phytochemicals screening was carried out which reveals the presence of alkaloids, tannins, phenols and flavonoids in studied plant extract. The nutritional analysis indicated that C. album may be a rich source of carbohydrate. Bangladesh J. Bot. 50(2): 417-421, 2021 (June)